Heteroatomic interface engineering of an octahedron VSe2–ZrO2/C/MXene composite derived from a MXene-MOF hybrid as a superior-performance anode for lithium-ion batteries. Issue 6 (18th January 2023) - Li, Hanbin; Li, Jinliang; Ma, Liang; Zhang, Xinlu; Li, Junfeng; Li, Jiabao; Lu, Ting; Pan, Likun
Abstract : The VSe2 –ZrO2 /C/MXene composite derived from a MXene-MOF hybrid with excellent cycling stability and high reversible capacity exhibited satisfying lithium-ion storage performancedde. Abstract : As a promising electrode material with tremendous specific capacity, vanadium diselenide (VSe2 ) has recently attracted renewed attention. However, the application of VSe2 is still hindered by the difficulty in its synthesis and nature of volume expansion. In this work, we developed a practical solvothermal method and in situ selenization process to obtain the VSe2 –ZrO2 /C/MXene composite from the MXene-metal–organic framework (MOF) hybrid precursor. During the synthesis process, V2 CT x is converted to VSe2 /MXene, which firmly anchors on the porous carbon derived from UiO-66 with the assistance of another derivative ZrO2 via chemical bonding. Remarkably, benefitting from the practical cooperation between VSe2 /MXene, ZrO2 and porous carbon, VSe2 –ZrO2 /C/MXene displays an outstanding lithium storage performance with an enduring capacity rise from 461.2 to 1238.5 mA h g −1 at 100 mA g −1 after a short recession during cycling, which is investigated in detail as a "negative fading" phenomenon. Even at the high current density of 1.0 A g −1, the composite still presents a high reversible capacity of 430 mA h g −1 after 1000 cycles, highlighting its superior cycling stability. The application potential of the VSe2 –ZrO2 /C/MXene anode for LIBs has also been evaluated by assembling full cells. The strategy in this work inspires the construction design of novel selenide-based electrode materials for high-performance lithium-ion batteries.